Combined Therapy with microRNA-Expressing Salmonella and Irradiation in Melanoma - Wonsuck Yoon (MDPI AG, 2021)
Anticancer treatment strategies using bacteria as a vector are currently expanding with the development of anticancer drugs. Here, we present a research strategy to develop anticancer drugs using bacteria that contain miRNAs. We also present a strategy for the development of novel bacterial anticancer drugs in combination with radiation. Salmonella strains expressing miRNA were produced by modifying the miRNA expression vector encoding INHA, a radiation-resistant gene developed previously. The anticancer effect of INHA was confirmed using skin cancer cell lines. We also tested a combination strategy comprising bacteria and radiation for its anticancer efficacy against radiation-resistant mouse melanoma to increase the efficacy of radiation therapy as a novel strategy. The recombinant strain was confirmed to promote effective cell death even when combined with radiation therapy, which exerts its cytotoxicity by enhancing reactive oxygen species production. Moreover, a combination of bacterial and radiation therapy enhanced radiotherapy efficacy. When combined with radiation therapy, bacterial therapy exhibited effective anti-cancer properties even when administered to animals harboring radiation-resistant tumors. This strategy may promote the secretion of cytokines in cells and more effectively reduce the number of bacteria remaining in the animal. Thus, this study may lead to the development of a strategy to improve the effectiveness of radiation therapy using Salmonella expressing cancer-specific miRNA for intractable cancers such as those resistant to radiation.